Downregulated lncRNA HOTAIR inhibits the proliferation of granulosa cells in endometriosis by upregulating p21: lncRNA HOTAIR in endometriosis - Ye, Huayang; Lin, Yanshan; Wang, Yanfang; Xing, Jia; Zhang, Jun (Cellular and Molecular Biology, 2023)
This study was carried out to elucidate the biological function of HOTAIR in granulosa cells of endometriosis and the underlying mechanism. Granulosa cells were extracted from endometriosis patients and subjects with fallopian tube factor alone who received IVF-ET. Relative levels of HOTAIR and p21 in the extracted granulosa cells were determined by quantitative real-time polymerase chain reaction (qRT-PCR). Moreover, HOTAIR level in endometriosis patients in stage I-II or III-IV was determined. Regulatory effects of HOTAIR on the proliferation of KGN cells were evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide), 5-Ethynyl-2’- deoxyuridine (EdU) and colony formation assay. Flow cytometry was conducted to evaluate the potential influence of HOTAIR on apoptosis of KGN cells. The interaction between HOTAIR and EZH2, SUV12 was detected by RNA binding protein immunoprecipitation (RIP) and chromatin immunoprecipitation (ChIP) assay. Finally, the potential role of the HOTAIR/p21 axis in mediating cellular behaviors of KGN cells was explored. HOTAIR was downregulated in granulosa cells extracted from endometriosis patients relative to those with fallopian tube factor alone who received IVF-ET. Knockdown of HOTAIR suppressed the proliferative ability and induced apoptosis of KGN cells. RIP and ChIP assay showed that silence of HOTAIR released EZH2 to suppress the DNA methylation of p21. Knockdown of p21 could reverse the regulatory effect of HOTAIR on the proliferative change of KGN cells. Downregulated HOTAIR suppresses the proliferative ability and induces apoptosis of granulosa cells in endometriosis by upregulating p21.